LIFE HISTORY, WORK AND LIFE PROJECT (Fiep Bulletin - online, 2012)
This research sought to explore the meaning of work that was modified throughout  the mankind's history, from an activity of self identification and personal expression, to a way to consumerism wich is to capitalism a basic need. Suffocating the subjectivity and affections of individuals, promoting human exploration to the maintenance of a trained social unequal and unfair. The objective of this research was to evaluate the meanings produced  by the police road  before choosing their profession. Identify the entanglements between the life history, career choice and the feelings that permeate the work relationships. This study was performed with federal highway police in the city of João Pessoa / PB. The study included 13 federal highway polices, actively exercising their functions, in age from 50 to 59 years and with 11 to 20 years of service. The data were obtained by applying a semi-structured questionnaire for socio-demographic information and draw a profile of participants. The interviews were conducted individually with the use of a semi-structured questionnaire about the proposal. On the Meanings of Life History and Work, the data shows two interrelated classes: Class I. Survival and Social rise with 61.35% and Class II.  Life History, Life Project and Liberty with 38.65%. Demonstrating that the choice of profession has the personal experience as fundamental to the direction of their professional career. In this study, we found that the history of life can be an important tool to achieve the reality, the subjectivity of individuals and society. As well, the many difficulties, accompanied by a lack of psychological support to these professionals and showing up a situation of suffering for these individuals.
Keywords: Work; Life Project; exploration and survival.